Effect of dietary habits on the risk of metabolic syndrome: Yazd Healthy Heart Project. Issue 6 (13th December 2017) - Sarebanhassanabadi, Mohammadtaghi; Mirhosseini, Seyed Jalil; Mirzaei, Masoud; Namayandeh, Seyedeh Mahdieh; Soltani, Mohammad Hossein; Pakseresht, Mohammadreza; Pedarzadeh, Ali; Baramesipour, Zahra; Faraji, Reza; Salehi-Abargouei, Amin
Abstract: Objective: Metabolic syndrome (MetS) refers to a group of risk factors that increase the risk of cardiovascular mortality and morbidity. Dietary habits are among the most important risk factors for MetS. The current study aimed at assessing the effect of dietary habits on the risk of MetS in a 10-year follow-up study in central Iran. Design: Cohort study. Setting: Yazd, Iran. Subjects: Participants aged 20–74 years without any history of MetS, who were originally recruited for Yazd Healthy Heart Project (YHHP) during 2005–2006, were revisited during 2015–2016. At phase I of YHHP, demographic data, anthropometric measurements, five components of MetS, biochemical tests and dietary habits were evaluated; and the same data were collected in phase II. Results: A total of 1092 participants were eligible to be included in the present study. After follow-up, the 10-year cumulative incidence of MetS was 56·1 %. After adjustment for potential confounders, increased risk of MetS (hazard ratio; 95 % CI) was found in those who did not try to control their body weight (1·57; 1·06, 2·35), did not usually eat salad (1·91; 1·22, 3·00) and added salt to their food (1·57, 1·06, 2·33). These associations were stronger in men than in the total population after subgroup analysis, but were not present in women. Conclusions: Dietary habits affect the risk of MetS in the Iranian population. Lifestyle interventions are needed to improve dietary habits to reduce the risk of MetS. Future studies are highly recommended to confirm our results in other populations.